2003
DOI: 10.1046/j.1365-3059.2003.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in genotype, pathotype and anastomosis groups of Colletotrichum lindemuthianum isolates from Mexico

Abstract: Patterns of variation were determined in anastomosis, pathotype and genotype of Colletotrichum lindemuthianum samples collected from individual plants of common bean cultivars from four locations in the Mexican highlands. In Chihuahua, 22 polymorphic AFLP bands in isolates taken from a single plant identified five distinct genotypes. In Michoacán, nine genotypes were identified based on a total of only six polymorphic bands. Combined cluster analysis of all isolates from individual plants grouped them geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 16 publications
(21 reference statements)
6
38
1
Order By: Relevance
“…Based on the clustering of similarity estimates for anastomosis, a high number of anastomosis groups were observed within C. lindemuthianum race 65, however, of the 13 isolates investigated only three (LV58, LV61 and LV73) belonged to the same anastomosis group. Similar results have been reported by Rodriguez-Guerra et al (2003) who observed no pathogenic variability in different isolates collected from the same plant, although there was a great variation in the number of anastomosis groups. These authors pointed out that several anastomosis groups could be identified in natural populations and suggested that this might be a mechanism for the formation of different C. lindemuthianum clonal lineages.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the clustering of similarity estimates for anastomosis, a high number of anastomosis groups were observed within C. lindemuthianum race 65, however, of the 13 isolates investigated only three (LV58, LV61 and LV73) belonged to the same anastomosis group. Similar results have been reported by Rodriguez-Guerra et al (2003) who observed no pathogenic variability in different isolates collected from the same plant, although there was a great variation in the number of anastomosis groups. These authors pointed out that several anastomosis groups could be identified in natural populations and suggested that this might be a mechanism for the formation of different C. lindemuthianum clonal lineages.…”
Section: Discussionsupporting
confidence: 90%
“…One possible reason for the different levels of genetic diversity observed in each of the populations that we examined is that the pathogen interacts with the different host cultivars at each location and consequently interacts with different genetic backgrounds. In this case, the host diversity would influence the maintenance of the genotype diversity of the pathogen (Rodríguez-Guerra et al, 2003). The differences observed between populations are consistent with the fact that they did not produce compatible crosses, suggesting reproductive isolation between the five populations, which resulted in significant variability between the different sample locations.…”
Section: Discussionsupporting
confidence: 63%
“…In other words, the populations exhibit gametic equilibrium, suggesting that at some points during the host cycle, the pathogen undergoes sexual reproduction (Rodríguez-Guerra et al, 2003). Sexual reproduction allows for the generation of new combinations of alleles in each recombination cycle, leading to a high level of genetic diversity in the pathogen's population.…”
Section: Introductionmentioning
confidence: 99%
“…The high pathogenic variability revealed by C. lindemuthianum, which has not been completely elucidated, is attributed to its parasexual cycle (Rodríguez-Guerra et al, 2004). The pathogen's reproduction mechanism is responsible for continuous resistance enhancement, mainly observed in commercial cultivars, since most of them present monogenic resistance that is easily overcame by emerging races (Rodríguez-Guerra et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogen's reproduction mechanism is responsible for continuous resistance enhancement, mainly observed in commercial cultivars, since most of them present monogenic resistance that is easily overcame by emerging races (Rodríguez-Guerra et al, 2003). However, among the diverse strategies adopted to control anthracnose, genetic resistance is considered the most efficient and economical (Mahuku et al, 2002).…”
Section: Introductionmentioning
confidence: 99%